2021
DOI: 10.1186/s13717-021-00302-8
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in bird community assembly over medium-term along rural-urban gradients in Argentina

Abstract: Background The analysis of bird community assembly rules is fundamental to understand which mechanisms determine the composition of bird species in urban areas. However, the long-term variation of community assembly rules has not been analyzed yet. The objectives of this study are (1) to analyze the variation of community assembly rules along rural-urban gradients of three cities in central Argentina and (2) to compare the patterns of community assembly between two periods separated by 6 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
1
4
0
3
Order By: Relevance
“…Besides its inherent value, functional and phylogenetic diversity hold conceptual relevance for community ecology since functional and phylogenetic clustering patterns can provide insights into community assembly mechanisms such as the environmental filtering of species from the regional species pool (Weiher, 2011). So far, there is evidence that suggests that urban areas may be acting as filters for some lineages and functional traits (Sol et al, 2017;Leveau, 2021). To test this, departure from randomness is assessed through the comparison of observed values against random expectations obtained from null models that take into account differences in species richness (Swenson, 2014; for an example see Weideman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides its inherent value, functional and phylogenetic diversity hold conceptual relevance for community ecology since functional and phylogenetic clustering patterns can provide insights into community assembly mechanisms such as the environmental filtering of species from the regional species pool (Weiher, 2011). So far, there is evidence that suggests that urban areas may be acting as filters for some lineages and functional traits (Sol et al, 2017;Leveau, 2021). To test this, departure from randomness is assessed through the comparison of observed values against random expectations obtained from null models that take into account differences in species richness (Swenson, 2014; for an example see Weideman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although species population trends are not directly informative on drivers of population changes [ 21 ], observing a common trend among species with similar ecological or life history traits can provide the foundation to test specific hypotheses about the drivers of the observed population dynamics [ 22 ]. Despite the arising attention of a trait-based approach in community ecology [ 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and population ecology [ 30 , 31 , 32 , 33 , 34 ], only in the last few years researchers have started to explore the link between traits and population trends in avifauna over long time periods, highlighting the existence of different patterns among distinct functional groups [ 22 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hakkoum et al ( 2021 ) found that the input of organic matter and nutrients from the treated wastewater can increase the biodiversity of soil cyanobacteria, but municipal and mining solid wastes lead to decrease of diversity and microalgal biomass. Leveau ( 2021 ) found that environmental filtering by urbanization led to phylogenetical randomness and functional clustering of bird communities in urban habitats. By comparing nutrient cycling and litter decomposition between the litter of a single species and a mixed composition of litter in urban parks in São Paulo City, Brazil, Ferreira et al ( 2021 ) found that both environmental and biogeographic characteristics of the species shall be considered in urban reforestation programs.…”
Section: Linking Landscape and Environmental Changes To Ecological Pr...mentioning
confidence: 99%